CREATIVITY OF PRESCHOOL CHILDREN REVIVAL THROUGH INTERACTIVE METHODS (American Journal of Pedagogical and Educational Research, 2023)
The article highlights the issues of effective use by teachers of interactive methods in the organization of the pedagogical process in the formation of intellectual abilities in children in preschool educational institutions.